EXPLANATION NEEDED
1) Find the slope, x-intercept and y-intercept of line 4x - 6y - 24 = 0.
{answer should come  \frac{2}{3}, 6, -4}

2) Reduce the equation 3x - 2y + 6 = 0 to the double-intercept form and find the x-intercept and y-intercept. {answer should come \frac{x}{-2} +\frac{y}{3}=1, (-2), 3}

3) Th centroid of a triangle is (1,4) and co-ordinates of two of its vertices are (4,-3) and (-9,7). Find the area of the triangle. (answer should come 183/2)

1

Answers

The Brainliest Answer!
2015-01-14T18:16:45+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
4x - 6 y - 24 =0
divide by  the constant term and write it so that RHS has value 1.
   x / 6 - y / 4 = 1 
x intercept is 6  and  y intercept is 4.

write y term on LHS and x term and constant on the RHS.
   6 y = 4  x  - 24        =>       y =  2/3  x  - 4
     slope is  2/3...          OR, slope =  - (coeff of x ) / (coeff of y)
==========================
3 x - 2y + 6 = 0
     =>   y / 3 - x / 2 = 1
       =>  x intercept = - 2      and    y intercept = 3
===================
x coordinate of centroid = 1 = average of x - coordinates of three vertices
y coordinate of centroid = 4 = average of y - coordinates of three vertices

Let the coordinates of the third vertex C be = (x3,y3)
         1 = (4-9+x3) / 3        => x = 8
         4 = (-3+7+y3) / 3  => y = 0

use the formula for the area of triangle in terms of coordinates of the vertices.

  area = | x1 (y2 - y3) + x2 (y3 - y1) + x3 (y1 - y2) | / 2
         = | 4 (7 - 0) - 9 ( 0 +3 ) + 8 ( -3 - 7 ) | / 2
       = 79/2

OR,  by finding the lengths of sides as,
      AC² = (8-4)² + (0+3)² = 5²
      BC² = (8+9)²+(0+7)² = 338 = 13² * 2
      AB² = (9+4)²+(7+3)²  = 269
s = semi perimeter = (5 + 13√2 + √269) / 2
the area of the triangle could be found using the formula √[ s(s-a)(s-b)(s-c) ]


5 4 5
sir pleas answer brainly.in/question/71512